Fundamental Reform of Income Tax: In How Far Can the Assessment Basis Be Broadened and Tax Law Simplified? - Stefan Bach (Weekly Report, 2005)
Intensive discussion is now underway on the tax reform concept put forward by Paul Kirchhof. Analyses based on extrapolations of individual tax return data from the income tax statistics show that ending the main tax concessions and allowances would not be enough to compensate for the loss of revenue from lowering the top rate of tax to 25%. Moreover, the importance of simplifying the tax system is being exaggerated in public discussion. A much simpler tax system is neither necessarily efficient nor fair. Politicians must look for reasonable compromises here. With the appointment of Paul Kirchhof, Professor of Tax Law and former Judge at the Constitutional Court, to the Union parties' competence team the discussion on fundamental reform and simplification of the German income and corporate tax system has intensified. Kirchhof has put forward the most far-reaching proposal for tax reform of recent years in a concept developed with his research group on the Federal tax code. He wants to see an almost flat rate income tax of 25% on all taxable income over euro 18 000; in return, all tax concessions and exemptions related to specific types of income would be dropped, while lump sums would be allowed for some income-related expenses and operating expenditure. The tax regulations would also be tightened and their application simplified by thoroughly systematizing and redrafting the income tax laws. DIW Berlin carried out a study of this and other proposed reforms in April 2004 in regard to the revenue they would yield and their distribution effects, as well as their effects on the supply of labour. The main conclusion was that a clear drop in the rates of tax, particularly in the upper incomes range, would cause considerable loss of revenue, and that this could not be made good by broadening the tax base or stimulating growth. The proposals by Paul Kirchhof, as well as the concept put forward by the Free Democrats, would mean that tax payers on high incomes would pay very much less tax, not only in absolute terms but also in relation to their incomes, than tax payers on average earnings, so these proposals would also lead to greater inequality of income. In view of the current discussion on the scope for broadening the tax base a consideration of the main concessions and allowances is of interest. These are shown in the tax statistics or can be estimated from (table). An extensive and representative random sample was taken from the income tax statistics for 1998 - the latest year for which data is as yet available - and the key features that are relevant for taxation policy were extrapolated to the year 2005.4 According to the forecast 29 million tax payers will be liable for income tax in 2005, of whom 14.8 million will be single and 14.2 million married couples taxed on their joint incomes.5 Simulation calculations of the income tax charged for the 2005 tax year using DIW Berlin's income tax micro-simulation model are in line with the current tax revenue and current estimates of tax. Revenue from income tax charged will be euro 171.4 billions, and revenue from non-assessed nonassessed wage tax euro 15.1 billions.
Keywords: 330